Analysis of student misconceptions on cell material as the smallest unit of life - Oky Rizkiana Silaban; Hendro Pranoto (Universitas Negeri Jakarta, 2022)
This study aims to determine students' misconceptions on cell material as the smallest unit of life and the factors that cause misconceptions. The research method used was descriptive quantitative. The sample in this research amounted to 35 students who were taken using random sampling techniques. The four-tier diagnostic test was used as an instrument to determine students' misconceptions and the factors that caused the misconceptions were known through interviews. The results showed that students experienced misconceptions in the amount of 36.03% with the moderate category, where the highest misconception occurred in the indicator of analyzing the membrane transport mechanism by 48.57%, and the lowest misconception occurred in the indicator explaining the chemical components of a cell by 28.57%. The main factors causing misconceptions were are textbooks, friends, and the internet.